The Influence of Government Policy on the Management of Border Conflict between Indonesia and Oecusse District, Timor Leste - Kase, Petrus; M. Tamunu, Lenny; E. Oiladang, Chrisistomus; W. Tadeus, Dhey (International Journal of Engineering and Technology, 2018)
Although the government of Indonesia and Timor Leste have conducted a number of policy decisions and actions to manage border conflict between Indonesia and Oecusse District, Timor Leste, the conflict remains unresolved and has the potential to continue. This study examines the influence of government policy on the management of border conflict between the two countries. Data obtained from questionnaires were analysed statistically descriptive, and through Pearson correlation and simple linear regression. The findings show that Indonesian government policy decisions and actions are slightly slow and less equal in acting on managing the border conflict, and less clear in implementing border line regulation between the two countries, but has high ability to prevent the conflict escalation. Customary figures who live in the border conflict region highly agree with and suggest to the government of both sides the use of customary law/oath as policy alternative in managing the conflict but the suggestion remains less responded well. This study also reveals that Indonesian government policy positively and moderately correlates, however, its influence on management of the border conflict is 33.5%. The government of Indonesia needs to improve its policy decisions and actions to manage the border conflict so that can prevent well the potential of the conflict continuation.Â Â